2001
DOI: 10.5194/angeo-19-975-2001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of vertical eddy diffusivity in the troposphere, lower stratosphere and mesosphere over a tropical station

Abstract: Abstract. Long-term VHF radar (53 MHz with 3 • beamwidth) observations at Gadanki (13.5 • N, 79.2 • E), India, during the period from September 1995 to August 1999 are used to study monthly, seasonal and annual medians of vertical eddy diffusivity, K in the troposphere, lower stratosphere and mesosphere. First, the spectral width contribution due to non-turbulent effects has been removed for further analysis and the monthly, seasonal medians of K are calculated. The monthly median of K in the troposphere shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Figure 2c shows that the AO and SAO in percent differences have been removed but there are still higher-frequency oscillations with magnitudes below 5%. This is consistent with past studies showing AO and SAO in eddy diffusion coefficients [Kirchhoff and Clemesha, 1983;Fukao et al, 1994;Lübken, 1997;Khattatov et al, 1997;Rao et al, 2001;Sasi and Vijayan, 2001]. Our estimated K zzC profiles exhibit AO and SAO.…”
Section: Altitudinal Variation Of Global-mean Co 2 and K Zzsupporting
confidence: 93%
“…Figure 2c shows that the AO and SAO in percent differences have been removed but there are still higher-frequency oscillations with magnitudes below 5%. This is consistent with past studies showing AO and SAO in eddy diffusion coefficients [Kirchhoff and Clemesha, 1983;Fukao et al, 1994;Lübken, 1997;Khattatov et al, 1997;Rao et al, 2001;Sasi and Vijayan, 2001]. Our estimated K zzC profiles exhibit AO and SAO.…”
Section: Altitudinal Variation Of Global-mean Co 2 and K Zzsupporting
confidence: 93%
“…Various features of LAWP at Gadanki are given by Krishna Reddy et al (2001). Many researchers have examined the possibility of deducing the turbulence parameters like eddy dissipation rate (e) and eddy diffusivity (K h ) from the observed Doppler spectrum of the wind profiler (e.g., Gage and Balsley, 1978;Gossard, 1990;Gage, 1990;Narayana Rao et al, 2001;Satheesan and Krishna Murthy, 2002). One of the limitations of UHF radar for the studies on atmospheric turbulence is its sensitivity to the hydrometeors.…”
Section: Introductionmentioning
confidence: 99%
“…The Indian MST radar at Gadanki (13.5 • N, 79.2 • E) detects echoes from mesospheric altitudes during noon hours (Rao et al, 2001). A climatological study by Kumar et al (2007) has revealed the main characteristics of LLME in terms of occurrence, strength, altitude and seasonal dependencies.…”
Section: Introductionmentioning
confidence: 99%